The nexus between agriculture and nutrition: Do growth patterns and conditional factors matter? - Fan, Shenggen; Brzeska, Joanna (International Food Policy Research Institute, 2011)
This brief examines how different growth patterns lead to different nutritional outcomes and identifies the factors that influence the magnitude of this relationship. It aims to offer researchers insights on areas for future research and analysis and provide policymakers with potential development strategies and investment policies that will increase the likelihood of positive nutritional outcomes.